Evaluation of the sky quality at two Argentinian Astronomical Sites - Aube, M.; Fortin, N.; Turcotte, S.; Garcia, Beatriz Elena; Mancilla, Alexis Javier; Maya, Juan Augusto (Astronomical Society of the Pacific, 2014)
Fil: Aube, M.. University Of Sherbrooke; Canadá. Laval University; Canadá